Corporate entrepreneurship - Jerome A. Katz; Dean A. Shepherd (Advances in entrepreneurship, firm emergence and growth ;, 2004)
With an established body of literature on innovation and corporate entrepreneurship, this volume of Advances in Entrepreneurship, Firm Emergence and Growth turns to some of the leading and most promising scholars in the field to map out where we have been and provide some direction on where scholarship on this topic should proceed in the future. Topics include: a review of theory, research, and practice on corporate entrepreneurship and the behavior of managers; the central problems of managing innovation and corporate entrepreneurship and the central problems of longitudinal research on the topic; the different theoretical lens for investigating corporate entrepreneurship and the resulting research possibilities; a general systems perspective for exploring the relationship among strategy-structure-performance and corporate entrepreneurship; and international corporate entrepreneurship in terms of a knowledge-based source of competitive advantage and implications for a model of human resource management. This volume also continues the discussion of previous volumes with a provocative discussion of how to advance the field of entrepreneurship by Bill Gartner and a commentary and response to work on a signal detection theory approach to entrepreneurship.